KEEFEKTIFAN MODEL STUDENT TEAM ACHIEVEMENT DIVISION (STAD) DAN E-LEARNING PADA MATERI OPERASI PENJUMLAHAN DAN PENGURANGAN PECAHAN DI SEKOLAH DASAR - Sri Kadarwati; Kasni Astutik; Edi Prayitno (Jurnal Karya Pendidikan Matematika, 2018)
The low learning outcomes of Addition and Reduction of Fractions in class IV are partly due to: (1) a tedious learning process, (2) lack of use of ICT as a source and media of learning. To overcome this problem the research team developed student-centered learning through e-learning learning in the Student Team Achievement Division (STAD) model. This study is a true experiment using the Pre-Test Group Control Post Test Design. The population is Sambiroto 02 elementary school students as many as 75 students in the 2017/2018 school year. The E2 group with EAD learning using the STAD model reached the highest mean value of the three groups, amounting to 88.67, followed by the E1 group with STAD learning at 74.54 and the K group with expository learning at 63.10. Regression analysis showed a positive relationship between motivation and activity with learning outcomes in groups E1 and E2 so it can be concluded that the higher the student's motivation and activity score the higher the student's learning achievement in addition and subtraction operations in elementary schools.